Bacterial contaminants in chicken eggs available from various sources: Bacterial Contamination in Chicken Eggs from Multiple Sources - Kaldate, A R; Gandge, R S; Zende, R J; Desai, Deepashree N.; Pharande, R R (Indian Journal of Poultry Science, 2025)
Microbial contamination of eggs significant impact on poultry industry and poses a serious public health problem risk globally In present study a  total of 40 chicken egg samples, comprising  10 eggs each from a poultry farm, wholesaler shop, retail shop, and directly from a transportation vehicle delivering eggs from farm to wholesaler. The mean Total Viable Count (TVC) on eggshell surfaces was 106.20, 168.00, 165.00 and 250.00×104 CFU/ml respectivelyThe TVC on poultry farms eggsshells was significantly  higher (P≤0.01, while wholesaler shop eggs recorded significantly lower TVC (P≤0.01) compared to other sources.The  TVC differences between eggs from retailer shops and transportation vehicles were not statistically significant. No microbial growth was detected  in the egg contents of the any samples. Among the  40 eggshell samples, 30/40 (75%) yielded various Staphylococcus spp isolates including  Staphylococcus lentus in 12/40 (40%), Staphylococcus xylosus in 9/40 (30%), Staphylococcus kloosii in 2/40 (7%), Staphylococcus sciuri in 7/40 (23%). The remaining 10/40 (25%) isolates were Proteus spp 4, Citrobacter spp. 2, and Klebsiella spp 4 were. All 30 Staphylococcus spp isolates tested negative for biofilm production on Congo red agar and presence of  the Nuc gene via PCR amplification. Antibiotic sensitivity tests on 40 isolates using disc diffusion method revealed that Staphylococcus spp isolates were sensitive to Ciprofloxacin, Vancomycin, Gentamicin, but resistance to Penicillin and Erythromycin. Proteus spp, Klebsiella spp, and Citrobacter spp. were sensitive to Ciprofloxacin, Gentamicin, Neomycin and resistant to Penicillin and Erythromycin.